2019
DOI: 10.2196/14676
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Patient Simulations in Health Professions Education: Systematic Review and Meta-Analysis by the Digital Health Education Collaboration

Abstract: Background Virtual patients are interactive digital simulations of clinical scenarios for the purpose of health professions education. There is no current collated evidence on the effectiveness of this form of education. Objective The goal of this study was to evaluate the effectiveness of virtual patients compared with traditional education, blended with traditional education, compared with other types of digital education, and design variants of virtual patients in he… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
198
0
10

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 266 publications
(254 citation statements)
references
References 101 publications
(355 reference statements)
6
198
0
10
Order By: Relevance
“…Five of these twelve studies (26,38,(43)(44)(45) showed results equal to the control group. One of these twelve studies showed results in favour to traditional classroom teaching (30).This leaves a somewhat mixed impression of the effects of different learning designs and is in line with another review regarding different learning designs (3,21).…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Five of these twelve studies (26,38,(43)(44)(45) showed results equal to the control group. One of these twelve studies showed results in favour to traditional classroom teaching (30).This leaves a somewhat mixed impression of the effects of different learning designs and is in line with another review regarding different learning designs (3,21).…”
Section: Discussionsupporting
confidence: 73%
“…For example, using virtual patients in the learning design, evidence shows that when compared with traditional teaching, virtual patients can more effectively improve students' skills, and at least as effectively improve students' knowledge (20). To our knowledge, there is only one systematic review from 2015 that summarizes studies on effects of digital learning technology in physiotherapy education (21). The results showed that online technology (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The implementation of virtual patient cases is helping to develop clinical reasoning skills but makes it harder for students to develop physical examination skills, and this will be one of the greatest difficulties that students from the clinical years will face. 3 Even with online classes, not all in-person course units can be replaced by digital tools. It Is widely recognized that, on its own, providing formal knowledge is not enough to train a clinical expert.…”
Section: What Are Medical Schools Doing?mentioning
confidence: 99%
“…Teaching medical decision making should target not only the diagnosis itself, but also the reasoning process, which involves the application of medical knowledge, knowledge structure and problem‐solving strategies. However, the clinical thinking process involves unconscious cognitive capacities, which makes teaching and learning in this field challenging 1 . The traditional pedagogies of clinical reasoning are lectures, group discussions, bedside and ambulatory encounters, and case studies.…”
Section: What Problems Were Addressed?mentioning
confidence: 99%